Gene therapy in wound healing using nanotechnology. Issue 2 (30th December 2020) - Pang, Calver; Fan, Ka Siu; Wei, Lanxuan; Kolar, Mallappa K
Abstract: Wound healing is a complex and highly regulated process that is susceptible to a variety of failures leading to delayed wound healing or chronic wounds. This is becoming an increasingly global burden on the healthcare system. Treatment of wounds has evolved considerably to overcome barriers to wound healing especially within the field of regenerative medicine that focuses on the replacement of tissues or organs. Improved understanding of the pathophysiology of wound healing has enabled current advances in technology to allow better optimization of microenvironment within wounds. This approach may help tackle wounds that are difficult to treat and help reduce the global burden of the disease. This article provides an overview of the physiology in wound healing and the application of gene therapy using nanotechnology in the management of wounds. Abstract : Figure illustrating the use of gene therapy and nanotechnology in wound healing.